Baló's concentric sclerosis associated with primary human herpesvirus 6 infection. Issue 12 (16th November 2005) - Pohl, D; Rostasy, K; Krone, B; Hanefeld, F
Abstract : Background: Baló's concentric sclerosis (BCS) is a demyelinating disorder believed to be a rare variant of multiple sclerosis (MS). Human herpesvirus 6 (HHV-6) is a highly neurotropic virus causing severe central nervous system (CNS) infections predominantly following reactivation of latent HHV-6 in immunocompromised individuals. Primary infection with HHV-6 usually occurs in early childhood manifesting as exanthema subitum. The clinical spectrum of primary infection in adolescents or adults has not yet been evaluated. Case report: A previously healthy 13 year old girl developed acute hemianopsia and anomia 5 days after an episode of fever and malaise of unknown origin. Cerebral MRI revealed three white matter lesions, one with ring-like contrast enhancement. Lumbar puncture showed mononuclear pleocytosis of 30 cells/µl, oligoclonal IgG, and a normal protein level. Follow up cerebral MRI scans revealed lamellar concentric hemispheric lesions characteristic of BCS. The first neurological symptoms of the patient coincided with primary HHV-6 CNS infection, diagnosed by a positive PCR test of the CSF together with seroconversion. Response to antiviral and corticosteroid treatment was only temporary, but immunoglobulin treatment has so far been followed by clinical stability for 30 months. Conclusions: To our knowledge, this is the first report both of an association between HHV-6 and BCS and of immunoglobulin treatment of BCS. A late primary infection with HHV-6 might be associated with BCS. Further studies in patients with this rare disease are needed to confirm this association and to evaluate the efficacy of antiviral and immunoglobulin treatment.